RANCANG BANGUN KHASANAH KEKAYAAN LOKAL MELALUI MESIN PENCACAH JERAMI PADI SEBAGAI MEDIA TANAM JAMUR TIRAM (JURNAL KEBANGSAAN RI, 2025)
The availability of sawdust as a growing medium for oyster mushrooms is becoming increasingly limited, thus alternative raw materials are needed. Rice straw, as an abundant agricultural waste, has potential for use, but requires chopping to an ideal size of 2–5 mm. This research designed and built a rice straw chopper with a 1 HP electric motor drive and a pulley-belt transmission system. The research methods included observations of mushroom farmers, literature studies, design planning, technical calculations (torque, power, capacity), prototype fabrication, and performance testing. The test results show that the machine's production capacity reaches 2.78–3.24 kg/hour with efficiency between 94–97% depending on the number of blades. The machine operates stably, produces cuts according to standards, and is easy to operate. These findings provide a practical solution for mushroom farmers in utilizing straw waste as an economically valuable growing medium.
Keywords: shredder, rice straw, oyster mushrooms, planting media, mechanical engineering